2018
DOI: 10.1039/c7nr06991j
|View full text |Cite
|
Sign up to set email alerts
|

Very high commutation quality factor and dielectric tunability in nanocomposite SrTiO3 thin films with Tc enhanced to >300 °C

Abstract: We report on nanoengineered SrTiO3–Sm2O3 nanocomposite thin films with the highest reported values of commutation quality factor (CQF or K-factor) of >2800 in SrTiO3 at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…A high and stable dielectric tunability (75% at 200 kV cm −1 ) and low dielectric loss values (tan δ < 0.01) were achieved at room temperature . In an STO:Sm 2 O 3 VAN, large dielectric constant tunability (49%), low tangent loss, high commutation quality factor (>2800) were reported in the SrTiO 3 phase . The large vertical tensile strain was attributed to the enhanced dielectric properties in BSTO and STO.…”
Section: Functionality Tuning Driven By Strain Defect and Interfacementioning
confidence: 87%
See 1 more Smart Citation
“…A high and stable dielectric tunability (75% at 200 kV cm −1 ) and low dielectric loss values (tan δ < 0.01) were achieved at room temperature . In an STO:Sm 2 O 3 VAN, large dielectric constant tunability (49%), low tangent loss, high commutation quality factor (>2800) were reported in the SrTiO 3 phase . The large vertical tensile strain was attributed to the enhanced dielectric properties in BSTO and STO.…”
Section: Functionality Tuning Driven By Strain Defect and Interfacementioning
confidence: 87%
“…It was found that the out‐of‐plane and in‐plane lattice parameters are 4.06 and 3.98 Å, respectively, indicating an out‐of‐plane tensile strain of 0.6% . Sangle et al synthesized STO:Sm 2 O 3 VANs with high tetragonality ( c / a ) (up to 1.023) in the STO phase . Owing to the large out‐of‐plane tensile strain, a T C up to 300 °C was observed in STO.…”
Section: Functionality Tuning Driven By Strain Defect and Interfacementioning
confidence: 99%
“…127 A very low dielectric loss (tan d B 0.01) and relative large dielectric tunability (49% at 400 kV cm À1 ) was further reported in SrTiO 3 :Sm 2 O 3 VAN film. 128 Yang et al explored BiFeO 3 :Sm 2 O 3 VAN films and found that dielectric loss and leakage current were reduced compared to plain BiFeO 3 films (Fig. 5c).…”
Section: Multi-ferroelectricity and Dielectricitymentioning
confidence: 98%
“…BaTiO3 基薄膜具有优异的铁电、介电和压电等 性能,可广泛应用于介电调谐器件、移相器、介电 电容器、存储器、能量收集器等电子器件中 [1][2][3][4][5] 。本 研究着重为介电调谐器件提供研究思路,该类器件 需要尽可能高的介电调谐率和尽可能低的介电损耗, 从而保证器件的高调谐范围、高品质因子(Figure of Merit, FOM)以及高信号传输效率 [6][7][8][9] 。因此,提高介 电调谐率并降低介电损耗成为其相关研究的重点。 介电损耗是制约介电调谐器件 应用的重要因素,降低介电损耗是提高调谐效 率的关键。通过两步放电等离子烧结制备晶粒取向 的钙钛矿陶瓷,然后通过设计层状结构使其产生位 错堆垛,能有效地消除陶瓷内部的氧空位,极大提 高其介电调谐率并有效地控制介电损耗 [10] 。另外, 也可通过对钙钛矿陶瓷进行掺杂,使其处于多相共 存的状态, 易于形成多重极化, 从而使材料在铁电、 介电等性能方面达到综合最优 [11][12] 。 近年来,包括介电调谐器件在内的电子元器件 趋向于小型化和集成化。提高薄膜材料的介电调谐 率和品质因子已经成为研究的重点。山东大学张伟 等 [6] 用磁控溅射法在 SrTiO3 基底上 700 ℃制备出了 不同晶体取向的外延 BaTiO3 铁电薄膜,当外延 BaTiO3 铁电薄膜取向为(110)时,介电调谐率和介电 损耗均达到最大值。 剑桥大学 SANGLE 等 [13] 通过对 顺电相的 SrTiO3 进行掺杂,在 SrTiO3 基底上 750 ℃ 制备出了高四方度的 SrTiO3-Sm2O3 纳米复合薄膜, 该薄膜有着优异的介电调谐率和品质因子。山东大 学 郝 兰 霞 等 [14] [17] 。此外,在硅上的低温溅射,又使得 BaTiO3 薄膜产生了面内的压缩应变 [17] 。结合这些结果,本 研究在低制备温度下在硅基底上获得了柱状纳米晶 [18] [17,20] [17,21] 。因此,500 ℃ 制备的 BaTiO3 薄膜晶粒尺寸较大。而 450 ℃对应 着较高的 "过冷度" , 晶粒的形核速率高于长大速率, 所以薄膜由数量较多的小晶粒组成 [17] [17] ,即 m = S + 0 ε r…”
unclassified